A comparison of digital and conventional sketching: implications for conceptual design ideation. (2016) - Self, James; Evans, Mark; Kim, Eun Jin
The study compared the use of digital and conventional sketching as influence upon conceptual design work. The results show a significantly increased focus of attention upon the sketching tool in the digital condition compared to conventional sketching with pen and paper. Both a statistical analysis and fine-grained qualitative comparison illustrate how increased frequencies of sketching tool focused activities resulted in both significantly more time spent in problem orientated work and the fragmentation of attempts to transition from problem definition to generative solution ideation. In contrast, reduced tool-focused activity in the conventional sketching condition appeared to provide opportunities for significantly increased solution ideation through design-driven moves to explore, reflect upon and develop solution propositions. The implications of a tool orientated focus of attention are discussed in terms of its impact upon reflective solution ideation during conceptual design.